Collaborative creation of a reference architecture for the implementation of data service platforms (2020)
Big Data refers to data set whose volume, velocity, and variety make it difficult to capture, manage and process using conventional technologies and tools. This concept is generating new needs in organizations to allow the capture, storage, and analysis of data with these characteristics and thus obtain relevant information for decision-making. A challenge for organizations is the implementation of an architecture that covers these needs, since they must consider the different existing technologies and must establish the policies for data governance that will be available to users. A reference architecture of a data analytics platform that is capable of decoupling from technological tools will be a guide that will allow organizations to define a path to achieve the management of these data and thus have effective tools for make decisions in the company. © 2020, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.